From the Edge of the Horizon - Dan Hoffman (Oz, 1992)
The remarkable aspect of the horizon-phenomena is the manner in which it gathers the conditions of sight and site. The horizon is the form which consciousness inscribes upon the surround, the manner of seeing that binds our thinking to the visual presence of our world.